THE BRACHIOPOD FAMILY LINOPRODUCTIDAE STEHLI FROM THE LOWER MOSCOVIAN OF THE MIDDLE CARBONIFEROUS OF THE MOSCOW REGION - Lazarev S.S. (My University, 2006)
The phylogeny and taxonomy of the brachiopod family Linoproductidae are revised. The change in the distributional pattern of spines and distinctive structure of the median lobe of the cardinal process are shown to be the main apomorphies in the family evolution. A new subfamily, Linispininae, and the included new genera, Linispinella and Linispinus, are described. In the nominotypical subfamily Linoproductinae, a new genus Linoproductoides and two new species included in this genus are described from the Vereiskian deposits of the Moscow Region. The new species Linispinus riparius (Trautschold), L. longus sp. nov., and L. staricensis (Ivanov) are described from the Kashirskian deposits. Another new species is tentatively described as "Linoproductus" kabanovi. © Pleiades Publishing, Inc. 2006.
Keywords: BRACHIOPODS; LINOPRODUCTIDAE; MIDDLE CARBONIFEROUS; MOSCOVIAN; MOSCOW REGION; Paleozoic::Carboniferous::Pennsylvanian::Middle::Moscovian; Палеозой::Каменноугольная::Средний::Московский